PEMBERIAN PAKAN KOMERSIL YANG BERBEDA TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP BENIH IKAN TAWES (Barbonymus gonionotus) - Mahendra Mahendra (Universitas Teuku Umar, 2018)
This research aims to know the influence of some kind of feed commercial optimal provided to the rate of growth and survival tawes fish (Barbonymus gonionotus). This research method using Random Design experiments with complete (RAL), consisting of four treatments and three replicates. The treatment given is Pellet P1= tipe PF1000, P2 = Pellet tipe PF 999, P3 = Pellet tipe PF 781, dan P4 = Pellet tipe FF 79-2. Parameters observed include the specific growth rate (SGR), the survival rate (SR), and as water quality data supporting. Results of the study showed The provision of commercial feed different has not been affecting the growth rate and survival rate tawes fish. From the results of this research Feed commercial with treatment p2 pellet type PF 999 is the Is the feed of which showed growth fish tawes which high value. Keywords: Potassium Karbonat, Growth, Survival, Oreochromis niloticus